Remote sensing from unoccupied aerial systems: Opportunities to enhance Arctic plant ecology in a changing climate. (14th August 2022) - Yang, Dedi; Morrison, Bailey D.; Davidson, Kenneth J.; Lamour, Julien; Li, Qianyu; Nelson, Peter R.; Hantson, Wouter; Hayes, Daniel J.; Swetnam, Tyson L.; McMahon, Andrew; Anderson, Jeremiah; Ely, Kim S.; et al.
Abstract: The Arctic is warming at a faster rate than any other biome on Earth, resulting in widespread changes in vegetation composition, structure and function that have important feedbacks to the global climate system. The heterogeneous nature of arctic landscapes creates challenges for monitoring and improving understanding of these ecosystems, as current efforts typically rely on ground, airborne or satellite‐based observations that are limited in space, time or pixel resolution. The use of remote sensing instruments on small unoccupied aerial systems (UASs) has emerged as an important tool to bridge the gap between detailed, but spatially limited ground‐level measurements, and lower resolution, but spatially extensive high‐altitude airborne and satellite observations. UASs allow researchers to view, describe and quantify vegetation dynamics at fine spatial scales (1–10 cm) over areas much larger than typical field plots. UASs can be deployed with a high degree of temporal flexibility, enabling observation across diurnal, seasonal and annual time‐scales. Here we review how established and emerging UAS remote sensing technologies can enhance arctic plant ecological research by quantifying fine‐scale vegetation patterns and processes, and by enhancing the ability to link ground‐based measurements with broader‐scale information obtained from airborne and satellite platforms. Synthesis . Improved ecological understanding and model representation of arctic vegetation is needed to forecast the fate of the Arctic in a rapidly changing climate. Observations from UASs provide an approach to address this need, however, the use of this technology in the Arctic currently remains limited. Here we share recommendations to better enable and encourage the use of UASs to improve the description, scaling and model representation of arctic vegetation. Abstract : Improved ecological understanding and model representation of arctic vegetation is needed to forecast the fate of the Arctic in a rapidly changing climate. Observations from unoccupied aerial systems (UASs) provide an approach to address this need, however, the use of this technology in the Arctic currently remains limited. Here we share recommendations to better enable and encourage the use of UASs to improve the description, scaling and model representation of arctic vegetation.